Terminação de cordeiros ao pé da mãe em pastagem cultivada de azevém (Lolium multiflorum L.) + trevo vermelho (Trifolium pratense L.) com e sem o emprego da alimentação privativa ao cordeiro - Santos, Maurício Fernandes dos (2007)
The experiment objectified the termination of lambs to the foot of the mother in pasture cultivated of ryegrass and red clover with and without creep-feeding to the lamb. Evaluations in the performance, characteristics of carcass, production of commercial cuts and production of the components had been carried through not-carcass in the lambs kept to the foot of the mother and submitted to the alimentary treatments: PAST = pasture cultivated of ryegrass and red clover; APT = pasture cultivated of ryegrass and red clover + creep-feeding to the lamb during all the period of use of the grass; AP42 = pasture cultivated of ryegrass and red clover + creep-feeding to the lamb from 42 days after beginning of the use of the grass. For all the evaluated parameters of the grass, did not have interaction (P>0.05) between treatment and period, did not have difference between treatments (P>0.05) for the parameters evaluated in the grass. Animals that had received creep-feeding had presented greater (P<0.05) profit of daily average weight and lesser (P<0.05) number of days to reach the weight established of slaughter in relation to that they had only remained in pasture. The components carcass had not differed (P>0.05) in the alimentary treatments. The weight of slaughter of 28 kg was only reached in 43, 71 and 86% of the animals of treatments PAST, AP42 and APT, respectively. The job of creep-feeding better does not provide to quality and nor carcass yield, for the lambs slaughtered with 28kg. In handling pastures of similar form, the creep-feeding promotes additive effect on the efficiency of termination of the animals.